Hearing status and static postural control of collegiate athletes - Brancaleone, M. P.; Talarico, M. K.; Boucher, L. C.; Yang, J.; Merfeld, D.; Onate, J. A. (Journal of Athletic Training, 2023)
Context Because of the close proximity of the cochlea, vestibular apparatus, and shared neurovascular structures, the static postural control of athletes who are deaf or hard of hearing (D/HoH) may be different from that of athletes who are hearing. Limited research is available to quantify differences between these athletes.